PENGARUH KOMUNIKASI TERHADAP MOTIVASI WANITA DALAM MELAKUKAN PERAWATAN KECANTIKAN: SUATU STUDI PADA KLINIK DINA AKUPUNKTUR & BEAUTY CARE SURABAYA - Nella, Fritzie Floberti; Darmawan, Arif; Rochim, Achludhin Ibnu (Universitas 17 Agustus 1945 Surabaya, 2015)
This study aimed to know and observe what is the motivation of women at doing treatment for beautyat the Dina’s Acupuncture Clinics & Beauty Care in Surabaya. This study is a qualitative and descriptivestudy using interview techniques as a source and data analysis techniques. The interview used informantas data source for the as many as 2 speakers from the clinic manager and three of clinic’s consumer atDina’s Acupuncture Clinics & Beauty Care in Surabaya. The results showed that women do treatmentsfor beauty in order to maintain their body and face healthy. The women also do treatments for beautybecause the motivation to change the shape to take some ideal forms. In general, women do treatmentsfor beauty because they want to achieve beauty and fitness in a career appearance and environment.Keywords: women, motivation, clinics, care, beauty